2016
DOI: 10.1007/s10792-016-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

Overcorrecting minus lens therapy in patients with intermittent exotropia: Should it be the first therapeutic choice?

Abstract: To evaluate medium-term outcomes of overminus lens treatment in patients with intermittent exotropia [X(T)]. A retrospective analysis was performed of the outcomes of 19 children with X(T) who were prescribed overminus lens (-2.00 to -4.00 D) for a median period of 18 months (6-33). The success was evaluated using two assessment methods: 1. Newcastle Control System (NCS), and 2. Jampolsky's assessment. The mean age of the patients was 6.8 ± 3.3 years (range 3-14 years). After the therapy, the median NCS score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
1
26
0
2
Order By: Relevance
“… 67 Minus lens therapy is usually used in preschool children (aged 2–7 years old); 37 41 however, there are reports of its efficacy in older ages, too. 40 68 It was previously believed that the minus lens was effective only in patients with a high AC/A; however, more recent evidence suggests otherwise. 20 40 56 57 On the other hand, recent studies found that a high AC/A ratio was not detrimental to a good outcome, and it appears that even children with low and normal AC/A ratios may respond well to overcorrecting minus lens therapy.…”
Section: R Esultsmentioning
confidence: 99%
“… 67 Minus lens therapy is usually used in preschool children (aged 2–7 years old); 37 41 however, there are reports of its efficacy in older ages, too. 40 68 It was previously believed that the minus lens was effective only in patients with a high AC/A; however, more recent evidence suggests otherwise. 20 40 56 57 On the other hand, recent studies found that a high AC/A ratio was not detrimental to a good outcome, and it appears that even children with low and normal AC/A ratios may respond well to overcorrecting minus lens therapy.…”
Section: R Esultsmentioning
confidence: 99%
“…1 The generally accepted goal of esotropia management is to achieve 10 prism diopters (PD) of orthotropia. 2,3 This will stimulate binocular fusion and maintain alignment in the absence of amblyopia. It can be achieved in those with fully accommodative esotropia with the full cycloplegic optical correction alone.…”
Section: Introductionmentioning
confidence: 99%
“…Different surgical procedures maybe used including: bilateral recession of the medial rectus muscles as procedure of choice, 4,5 though limited by the high variability in surgical dose-response 6 and three-horizontal muscle surgery (bilateral medial rectus recession and a lateral rectus resection in the non-dominant eye) for the correction of large-angle esotropia. 2,3 Bilateral posterior fixation of the medial rectus muscles has also been shown to give good results in patients with essential infantile esotropia showing overacting medial rectus muscles, variable angles, and non-accommodative convergence excess. This can be done as a single procedure 7 or to augment bilateral medial rectus recessions.…”
Section: Introductionmentioning
confidence: 99%
“…Исходя из принципов аккомодационно-конвергентной синкинезии, рядом авторов рассматривался вопрос о целесообразности применения гиперкоррекции в функциональном лечении содружественного косоглазия и экзофории [9][10][11][12]. Между тем многие аспекты данного направления являются в настоящее время недостаточно изученными.…”
Section: Introductionunclassified
“…Авторы указывали, что гиперкоррекция не являлась определяющим фактором возникновения или прогрессирования миопии у этих пациентов. При этом отмечен положительный эффект от использования гиперкоррекции и отсутствие астенопических явлений [10,11,16]. В нашей работе мы использовали гиперкоррекцию на первых этапах лечения только в процессе зрительных тренировок с целью создания наиболее благоприятных условий для взаимодействия всех компонентов бинокулярного механизма и развития фузионной способности.…”
unclassified